The Influence of Total Quality Management (TQM) and Organizational Culture on Employee Job Satisfaction that Impacts Employee Performance (Case Study on Cooperatives in South Tangerang City) - Hamsinah Hamsinah; Denok Sunarsi; Umi Narimawati; Afzal Sayed Munna; Avinash Pawar (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the effect of total quality management and organizational culture on employee job satisfaction with employee performance as an intervening variable. This research uses quantitative research, which is based on data that can be calculated to produce a strong quantitative interpretation. The data analysis technique used is PLS version 3.0 (Partial Least Square) software which is a variant-based structural equation analysis (Structural Equation Model) and can perform measurement model testing as well as structural model testing. The population and sample in this study were cooperatives in the South Tangerang area. The technique used in this study was the Simple Random Sampling Technique. And the sample used in this study were 191 employees in the South Tangerang Cooperative. With the results of the study that total quality management has a significant effect on employee job satisfaction because the t-statistic value is 19,056 1,652 while the latent variable on organizational culture has an effect on the contribution to the latent variable on employee job satisfaction with a statistical value of 14,351 1,652. While the latent variable total quality management has no significant effect on employee performance because the value is 1.281 1.652. And the organizational culture variable has an effect on employee performance with a t-statistic value of 4.214 1.652. And for the variable employee job satisfaction has an effect on employee performance with a value of 5.115 1.652.